Promoting intestinal IgA production in mice by oral administration with anthocyanins - Liu, Xuerun; Wang, Luoyang; Zhuang, Huiren; Yang, Zhenghuan; Jiang, Guoqiang; Liu, Zheng (Frontiers in Immunology, 2022)
While recent years have witnessed ever-growing evidence on the prebiotic attributes of anthocyanins for treatment of microbiota-associated diseases, the complex interplay between anthocyanin uptake, the gut microbiota, and the intestinal mucosal immune system remains poorly understood. Here, we investigate the effects of bilberry anthocyanins on the gut microbiota composition and metabolism, and the intestinal mucosal immune system of mice. We observed an increased proportion of IgA-producing plasma cells in the mesenteric lymph nodes (MLNs) and an enhanced secretion of secretory immunoglobulin A (sIgA) and antimicrobial peptides in the small intestine. Small intestine transcriptome analysis further suggested that anthocyanins influenced IgA production. We found that oral administration of anthocyanins altered the gut microbiota through maintaining the anaerobic intestinal environment, promoting the secretion of sIgA and antimicrobial peptides, and downregulating cell motility and mobile genetic elements of commensal bacteria. These observations suggest that the oral administration of anthocyanins helps in maintaining intestinal homeostasis and thus it may find applications in immunotherapy and related fields.